1989
DOI: 10.1007/bf00140133
|View full text |Cite
|
Sign up to set email alerts
|

Seroepizootology of Q fever in Bulgaria during the last five years

Abstract: The work presents results of investigations on Q fever seroepizootology in Bulgaria during the last five years. These data are compared with the preceding period from 1950 to 1983. The basic method for investigation is Complement fixation test. Also used are immunofluorescence, agglutination reaction, cultivation and direct Electron microscopy. In general 15,814 samples were tested. Q fever positivity was foundin 10.08% of cattle, 20.44% of sheep, 10.17% of goats, 59.25% of dogs, 26.66% of magpies, 11.11% of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 0 publications
0
8
1
Order By: Relevance
“…The increase of the seropositivity started in 1989 (2.85 %), and reached 4.76% (1994), followed by slight progressive increase during 1996-1997. The increase of the seropositivity rate could be a sign of an activation of natural and agricultural foci of Q-fever and also of the cyclic recurrence of the investigation (19). In earlier studies of Bulgarian authors (20,21) was found, that in some active agricultural foci of Q-fever with high spread of Coxiella burnetti among cattle, sheep and goats can be detected considerable seropositive rates among horses, up to 20 %.…”
mentioning
confidence: 89%
See 3 more Smart Citations
“…The increase of the seropositivity started in 1989 (2.85 %), and reached 4.76% (1994), followed by slight progressive increase during 1996-1997. The increase of the seropositivity rate could be a sign of an activation of natural and agricultural foci of Q-fever and also of the cyclic recurrence of the investigation (19). In earlier studies of Bulgarian authors (20,21) was found, that in some active agricultural foci of Q-fever with high spread of Coxiella burnetti among cattle, sheep and goats can be detected considerable seropositive rates among horses, up to 20 %.…”
mentioning
confidence: 89%
“…psittaci in equine infectious pathology have been carried out by S. P. Martinov (unpublished data). Studies on Q-fever in horses in Bulgaria were performed by several research groups (19,20,21). Some authors reported their results from studies on African Horse Sickness (4,5,6 The aim of the present work is to perform comparative etiological studies on the Equine Infectious Anaemia (EIA), Equine Rhinomneumonitis (ER), Equine Influenza (EI), Chlamydia psittaci infections (Chp.l) and Qfever (Qt) during the period of 1989-1997.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…al. (18). The sera which showed retention of the compliment at dilution of 1: 10 were further examined at ascending dilutions.…”
Section: -67 63mentioning
confidence: 99%